Coupling Multi-objective Constrained Optimization, Life Cycle Assessment, and Detailed Process Simulation for Potable Water Treatment Chains - Capitanescu, Florin; Igos, Elorri; Marvuglia, Antonino; Benetto, Enrico (Journal of Environmental Accounting and Management, 2026)
This paper deals with the optimization of key decision variables of a potable water production plant. To this end we propose a multi-objective constrained optimization approach which trades-off operational costs and environmental impact while satisfying outlet water drinkability criteria. The proposed solution approach consists in coupling a meta-heuristic global optimization algorithmand EVALEAU, which is a state-of-the-art process modelling - life cycle assessment (LCA) tool for simulating potable water treatment chains. The proposed eco-design optimization approach is successfully illustrated on a real-world model of a water production plant, and the relative performances of two highly praised stateof- the-art derivative-free global optimization algorithms,namely the Strength Pareto Evolutionary Algorithm (SPEA2) and Non-dominated Sorting Genetic Algorithm (NSGA-II),are compared.